Education on Risk Factors of Cerebrovascular Disease among the Community of Kuwue Village, Montasik Subdistrict, Aceh Besar - Desreza, Nanda; Rizkidawati, Rizkidawati; Putri, Annisa; Syafitri, Winda Artika (International Journal of Social Science and Community Service, 2025)
Cerebrovascular disease is a condition in which rapidly developing clinical signs in the form of focal and global neurological disorders appear. These signs can worsen and persist for more than 24 hours and can cause death. The aim of this activity is to increase public understanding of how to prevent this disease and reduce its complications. The venue for this event is Kuwue Montasik village in Aceh Besar. The Kuwue village community, consisting of 18 people, attended in person. This community service method was implemented through training and discussion. The activity began on 20 August 2025 at 10:00 a.m. and lasted until completion. Starting with participant data, the activity continued with a presentation of the objectives and material on the risk factors for this disease, better known as stroke, its triggers, and its complications. The activity showed that the community understood low-fibre diets, low physical activity, smoking, and excessive salt use in cooking. It was recommended that the community improve their lifestyle, diet, and rest patterns, and families should continue to provide strong motivation to family members who are vulnerable to danger. In addition, the responsibility of health workers to provide consistent education should be increased.